2018
DOI: 10.1136/esmoopen-2017-000301
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in cancer patients undergoing haemodialysis: a nationwide study in Japan

Abstract: BackgroundCancer is a major cause of death in patients undergoing haemodialysis. However, information about the actual clinical practice of chemotherapy for patients with cancer undergoing haemodialysis is lacking. We conducted a nationwide survey using questionnaires on the clinical practice of chemotherapy for such patients.Patients and methodsThe nationwide survey included patients undergoing haemodialysis who were subsequently diagnosed with cancer in 20 hospitals in Japan from January 2010 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…And these patients were less likely to survive when a complication occurred. As for chemotherapy, though it is not contraindicated in dialysis patients with cancer, its usage is considered low, with the rate of 28% in France [52], 24% in Australia [53], and 9% (for palliative purpose) in Japan [54]. In our HD patients, only one patient received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…And these patients were less likely to survive when a complication occurred. As for chemotherapy, though it is not contraindicated in dialysis patients with cancer, its usage is considered low, with the rate of 28% in France [52], 24% in Australia [53], and 9% (for palliative purpose) in Japan [54]. In our HD patients, only one patient received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with impaired renal function, 5FU can safely be administered without dose adjustments, as it is metabolized in the liver and not in the kidneys [9][10][11][12]. In a previous observational study, most cancer patients undergoing hemodialysis (HD) received 5FU without dose adjustments [13]. However, the elimination of α-fluoro-β-alanine (FBAL), a 5FU metabolite, is dependent on renal excretion [14].…”
Section: Introductionmentioning
confidence: 99%
“…This study reported the anticancer drugs prescribed and dosage adjustment in hemodialysis patients but did not mention the recommend dosages of the prescribed anticancer drugs. A nationwide survey of chemotherapy in cancer patients undergoing hemodialysis was also conducted in Japan (13). Among 107 patients with unresectable cancer, only 44 (41%) underwent chemotherapy, 36 (34%) received the best supportive care, and 27 (25%) underwent other therapies.…”
Section: Discussionmentioning
confidence: 99%